Iron and zinc biofortification in potato through the introduction of NICOTIANAMINE SYNTHASE and FERRITIN genes - Cortelezzi, Juan Ignacio (2025)
Micronutrient deficiencies, such as those involving iron, zinc, and vitamin A, represent a critical global public health challenge. Crop biofortification offers a costeffective solution by enhancing the micronutrient content of staple foods, particularly in regions with limited access to diverse diets. In this study, we developed a high-iron and high-zinc Spunta potato variety through the co-expression of the Arabidopsis thaliana NICOTIANAMINE SYNTHASE 1 (AtNAS1) gene under a constitutive promoter and the Phaseolus vulgaris FERRITIN (PvFERRITIN) gene under a tuber-specific promoter. Of the five co-expressing events evaluated, we identified FN4 as the optimal line, achieving significant levels of iron and zinc biofortification without compromising yield. This line exhibited an enhanced capacity to accumulate iron in tubers under conditions of increased soil iron availability, maintaining yield even when vegetative growth was reduced due to elevated soil iron levels. The FN4 variety showed a 2.1- and 1.8-fold increase in iron and zinc content, respectively, in the tubers. A typical portion of this variety could provide 33.3% of the recommended dietary allowance (RDA) for iron and 19.8% for zinc in women of reproductive age. This biofortified potato has the potential to reduce iron deficiency anemia and zinc deficiency, enhancing the health of populations in both rural and urban areas affected by poverty.